Differential Proteomic Profiling at Different Phases of Dengue Infection: An Intricate Insight from Proteins to Pathogenesis - Choudhury, Kamalika Roy; Verma, Priya; Ray, Aleepta Guha; Samanta, Sandip; Manna, Asish; Bandyopadhyay, Arun; Dutta, Shanta; Sadhukhan, Provash C. (Journal of proteome research, 2024)
Dengue fever is a rapidly emerging tropical disease and an important cause of morbidity in its severe form worldwide. A wide spectrum of the pathophysiology is associated with the transition of dengue fever to severe dengue, which is driven by the host immune response and might reflect in patients’ proteome profile. This study aims to analyze the plasma from different phases of dengue-infected patients at two time points. A mass-spectrometry-based proteomic approach was utilized to understand the involvement of probable candidate proteins toward developing a more severe, hemorrhagic form of dengue fever. Dengue-infected hospital-admitted patients with <5 days of fever were included in this study. Patient samples from the acute phase were screened for the presence of NS1 antigen using ELISA and subjected to molecular serotyping. Dengue molecular serotype-confirmed patient samples, pairwise from acute and critical phases with healthy control were subjected to qualitative and quantitative proteomic analysis, and then pathway analysis was performed. The protein–protein interaction network between the dengue virus and host proteins was depicted in the search for proteins associated with severe dengue pathophysiology. An array of apolipoprotein, cytokines, and endothelial proteins in association with virus replication and endothelial dysfunction were validated as biomolecules involved in severe dengue pathophysiology.